Molecular Evolution of Freshwater Snails with Contrasting Mating Systems. (14th May 2015) - Burgarella, Concetta; Gayral, Philippe; Ballenghien, Marion; Bernard, Aurélien; David, Patrice; Jarne, Philippe; Correa, Ana; Hurtrez-Boussès, Sylvie; Escobar, Juan; Galtier, Nicolas; Glémin, Sylvain
Abstract : Because mating systems affect population genetics and ecology, they are expected to impact the molecular evolution of species. Self-fertilizing species experience reduced effective population size, recombination rates, and heterozygosity, which in turn should decrease the efficacy of natural selection, both adaptive and purifying, and the strength of meiotic drive processes such as GC-biased gene conversion. The empirical evidence is only partly congruent with these predictions, depending on the analyzed species, some, but not all, of the expected effects have been observed. One possible reason is that self-fertilization is an evolutionary dead-end, so that most current selfers recently evolved self-fertilization, and their genome has not yet been strongly impacted by selfing. Here, we investigate the molecular evolution of two groups of freshwater snails in which mating systems have likely been stable for several millions of years. Analyzing coding sequence polymorphism, divergence, and expression levels, we report a strongly reduced genetic diversity, decreased efficacy of purifying selection, slower rate of adaptive evolution, and weakened codon usage bias/GC-biased gene conversion in the selfer Galba compared with the outcrosser Physa, in full agreement with theoretical expectations. Our results demonstrate that self-fertilization, when effective in the long run, is a major driver of population genomic and molecular evolutionary processes. Despite the genomic effects of selfing, Galba truncatula seems to escape the demographic consequences of the genetic load. We suggest that the particular ecology of the species may buffer the negative consequences of selfing, shedding new light on the dead-end hypothesis.